Kerangka Decision Support System Berbasis Aturan untuk Evaluasi Izin Mendirikan Bangunan di Kawasan Rawan Longsor dan Banjir Kasus Kabupaten Bogor - Dyah Sulistyowati Rahayu; Nenden Nuraini; Zidan Wali Arubusman; Chaerul Cahyadi (Jurnal Telematika, 2025)
Bogor Regency is highly vulnerable to landslides and floods due to its geomorphology, intense rainfall, and increasing development pressure. The demand for building permits (IMB/PBG) in this area poses a policy dilemma because residential development in vulnerable zones can increase the risk of losses. This study aims to develop a decision-support system (DSS) framework to assist the government in evaluating the feasibility of residential building permits in an objective, transparent, and risk-based manner. The research method uses a literature review approach to examine relevant feasibility criteria, including geotechnical and hydrological factors, as well as regulatory aspects. The synthesis results in a rule-based DSS framework with three decision outputs: Go (feasible), Special Mitigation (conditional permit with technical requirements such as stilt houses, pile foundations, or slope drainage), and No-Go (not feasible). The contribution of this research is to provide a conceptual DSS model that can be integrated with the Building Licensing System (SIMBG) to support policy consistency, strengthen disaster mitigation, and improve spatial planning accountability in Bogor Regency.